Residual effects of intercrop system and rice as mono crop on growth and yield of maize in rice-based production system - Nattawut, S.; Lampan, K.; Sukunya, Y.; Sudteerak, S.; Patcharaporn, S.; Potjana, S.; Nittaya, P. (International Journal of Agricultural Technology, 2020)
The plot previously planted with maize, peanut and sweet potato as intercropping system had higher organic matter, available phosphorus, exchangeable potassium, exchangeable magnesium extractable iron, manganese, zinc and copper, than the plot previously planted with rice as mono crop. The results suggested that intercropping system improved soil quality and might be beneficial to succeeding crops. Maize and rice grown after intercropping system were not significantly different for growth parameters, yield and yield components. Maize grown after intercropping system was better than its grown after rice because of higher yield (7,895 kg/ha and 8,558 kg/ha) for the plot after rice harvest and the plot after intercropping system. The results indicated that maize cultivation could be decreased in rice cultivation in irrigated areas of the dry season. It is possible the rice growers can select both systems.